The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13194792
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Following Re-Operations for Intracranial Meningioma

Abstract: The outcomes following re-operation for meningioma are poorly described. The aim of this study was to identify risk factors for a performance status outcome following a second operation for a recurrent meningioma. A retrospective, comparative cohort study was conducted. The primary outcome measure was World Health Organization performance. Secondary outcomes were complications, and overall and progression free survival (OS and PFS respectively). Baseline clinical characteristics, tumor details, and operation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These findings support those of Richardson et al, who reported a diminution in functional status in patients with recurrent intracranial meningiomas, irrespective of location or treatment modality. 40 Moreover, Magill et al demonstrated considerably higher rates of postoperative complications in patients receiving reoperation for recurrent SBM. 22 It has been argued that as patient age increases from first surgery, brain resilience and plasticity decrease, resulting in decreased functional status in these patients.…”
Section: Results In the Context Of The Literaturementioning
confidence: 99%
“…These findings support those of Richardson et al, who reported a diminution in functional status in patients with recurrent intracranial meningiomas, irrespective of location or treatment modality. 40 Moreover, Magill et al demonstrated considerably higher rates of postoperative complications in patients receiving reoperation for recurrent SBM. 22 It has been argued that as patient age increases from first surgery, brain resilience and plasticity decrease, resulting in decreased functional status in these patients.…”
Section: Results In the Context Of The Literaturementioning
confidence: 99%
“…N = 41 articles met the inclusion criteria and N = 16 articles failed to assess management of meningioma recurrence. Finally, N = 24 articles were included in our review [ 22 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 ] ( Flowchart 1 ). The articles were distributed as follows: studies on chemotherapy (N = 14); RT, PT, and SRS (N = 6); BNCT (N = 2); and surgery (N = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Richardson et al [ 53 ] investigated the outcomes of N = 56 patients who had re-operation for meningioma recurrence. The median time to re-operation after initial surgery was 35 months (95% CI 28.9–41.1), while it was 68 months (95% CI 49.1–86.9) after re-operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the relatively indolent nature of most meningioma, ‘active monitoring’ of the residual tumor was used for most patients, and this approach is supported by the finding that very few patients had clinical progression associated with radiological growth. 28,29 Elevated Ki-67 index has previously been noted to predict time to recurrence in a prospective cohort of surgically treated meningioma consisting of both GTR and STR cases 30 ; however, this was only available for 20 patients within our study, likely representing a highly selected population. Radiation-induced meningiomas have been noted to display increased volumetric growth rates, in comparison with sporadic meningiomas, hence why they were not included in our study.…”
Section: Discussionmentioning
confidence: 98%